The neural elements in the lining of the ventricular-subventricular zone: making an old story new by high-resolution scanning electron microscopy - Haemmerle, Carlos Alexandre dos Santos; Nogueira, Maria Inês; Watanabe, Ii-sei (Frontiers in Neuroanatomy, 2015)
The classical description of the neural elements that compose the lining of brain ventricles introduces us to the single layer of ependymal cells. However, new findings, especially in the lateral ventricle - the major niche for the generation of new neurons in the adult brain - have provided information about additional cell elements that influence the organization of this part of the ventricular system and produce important contributions to neurogenesis. To complement the cell neurochemistry findings, we present a three-dimensional in situ description that demonstrates the anatomical details of the different types of ciliated cells and the innervation of these elements. After processing adult rat brains for ultrastructural analysis by high-resolution scanning electron microscopy and transmission electron microscopy, we observed a heterogeneous pattern of cilia distribution at the different poles of the lateral ventricle surface. Furthermore, we describe the particular three-dimensional aspects of the ciliated cells of the lateral ventricle, in addition the fiber bundles and varicose axons surrounding these cells. Therefore, we provide a unique ultrastructural description of the three-dimensional in situ organization of the lateral ventricle surface, highlighting its innervation, to corroborate the available neurochemical and functional findings regarding the factors that regulate this neurogenic niche.